Neutrophil extracellular traps predict poor survival in cancer: a systematic review and meta-analysis of studies on tissue and circulating biomarkers - Lee, Seungwoo; Kim, Eun Young; Park, Woohyun; Lee, Young Sub; Yim, Kwangil (Frontiers in Immunology, 2025)
BackgroundNeutrophil extracellular traps (NETs) are fibrous, web like chromatin structures released by activated neutrophils that entrap and immobilize pathogens through histones, granule derived proteolytic enzymes, and myeloperoxidase (MPO) dependent mechanisms. Beyond host defense, NETs have been implicated in tumor progression; yet anticancer activity also has been reported, and findings vary across specimen types (tumor tissue versus blood) and detection methods, antibody panels, leaving their role in oncogenesis uncertain. We performed a systematic review and meta-analysis to define the prognostic significance of NETs in cancer, stratified by specimen type, detection technique, and antibody panels.MethodsFollowing PRISMA guidelines, we searched PubMed, EMBASE, and the Cochrane Library for studies published through August 10, 2023, that reported quantitative NET measurements linked to oncologic outcomes.ResultsFifteen studies (5,202 patients; publication years 2016–2023) reporting hazard ratios (HRs) for overall survival (OS) and disease free survival (DFS) relative to NET levels met inclusion criteria. Six studies evaluated tumor derived NETs in tissue and nine assessed circulating NETs in blood. Among tissue studies, two used immunohistochemistry for citrullinated histone H3 (H3Cit) alone, and four applied multiplex immunofluorescence for MPO/H3Cit or neutrophil elastase (NE)/H3Cit. Among blood studies, enzyme linked immunosorbent assays targeting MPO/DNA predominated, followed by H3Cit assays. Higher NET levels were significantly associated with worse OS (HR 1.80; 95% CI 1.35–2.41) and DFS (HR 2.26; 95% CI 1.82–2.82), irrespective of tissue or blood based measurement. Prognostic associations were robust for MPO/DNA, H3Cit, and NE, but not for cell free DNA.ConclusionElevated NET levels predict poorer outcomes in patients with cancer independent of specimen source and most analytic modalities (except cell free DNA), supporting NETs as a promising biomarker for risk stratification and precision oncologic decision making.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025596821.